The Potential Use of Degradable Starch Microspheres as a Carrier for Nasal Drug Administration - Unal,Rojda (2023)
Intranasal drug delivery is a practical and accessible method for treating localized symptoms as well as achieving systemic drug absorption. The approach takes advantage of the permeability, vascularization, and limited enzymatic activity of nasal tissue, leading to enhanced drug absorption. Moreover, drugs can bypass the blood-brain barrier and directly reach the brain through the olfactory route. Nasal powder formulations present advantages over liquids, including improved mucosal clearance resistance, simplified composition, larger administration doses, and improved formulation stability. In this study, four different types of degradable starch microspheres (DSM), namely DSM-A, DSM-S, DSM-T, and DSM-L were evaluated for their potential use as nasal drug formulations. Furthermore, the microspheres were combined with a breath-actuated powder inhaler, ICOone Nasal. Initially, the physicochemical characteristics of the DSM batches were assessed, followed by performance testing, where they were loaded into the device to investigate their delivery performance. Additionally, nasal deposition studies were conducted using a 3D-printed nasal cavity model. The results revealed that, among the DSM batches, DSM-A is the most favorable option for nasal drug delivery, while DSM-S is the least preferred. DSM-A consists of easily dispersible particles not prone to agglomeration, distinguishing it from the other batches, particularly DSM-S, which exhibits high cohesive properties. In dry storage conditions, all batches exhibit excellent flow properties. DSM-A demonstrates the highest flowability, while DSM-S shows the poorest resulting in lower and higher retention from the ICOone device respectively. Regarding deposition in the nasal cavity, all DSM batches display a similar pattern when used with the ICOone Nasal device. The powder primarily adheres to the nasal vestibule and atrium area, with no powder reaching the olfactory region. Notably, DSM-A exhibits an even distribution without agglomerates, whereas DSM-S shows the presence of agglomerates.
Keywords: Pharmaceutical technology; Nasal administration; Läkemedel; Pulverformiga bärare; Sfärer; Pulverinhalation; Bärarmaterial; Läkemedelseffektivitet; Pulverteknik; Partikelformulering; Nasal deposition